2015
DOI: 10.1111/nep.12526
|View full text |Cite
|
Sign up to set email alerts
|

Ezrin contributes to impaired podocyte migration and adhesion caused by advanced glycation end products

Abstract: These results show a role for ezrin in AGE-induced podocyte damage and suggest a new avenue for possible therapeutic intervention in diabetic nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Renal tubule epithelial cells play an indispensable part in glomerular filtration barrier [ 5 ]. The structural and functional integrity of renal tubule epithelial cells have close relation with the maintenance of glomerular filtration function [ 6 ]. Dysfunction of renal tubule epithelial cells would result in interstitial fibrosis, glomerulosclerosis as well as proteinuria.…”
Section: Introductionmentioning
confidence: 99%
“…Renal tubule epithelial cells play an indispensable part in glomerular filtration barrier [ 5 ]. The structural and functional integrity of renal tubule epithelial cells have close relation with the maintenance of glomerular filtration function [ 6 ]. Dysfunction of renal tubule epithelial cells would result in interstitial fibrosis, glomerulosclerosis as well as proteinuria.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that AGEs interact with the N-terminal domain of ezrin and inhibit its actions in proximal tubule cells (60). Notably, a previous study indicated that AGE treatment reduced podocyte adhesion to fibronectin and inhibited migration; however, ezrin overexpression completely reversed the AGE inhibition of podocyte adhesion to fibronectin and partially reversed AGE-induced inhibition of migration (61). This suggests that HG-induced podocyte injury may be mediated by an increased level of AGEs.…”
Section: Discussionmentioning
confidence: 99%
“…Ezrin and its phosphorylation site at T567 attracted our attention. Ezrin, a member of the Ezrin–Radixin–Moesin (ERM) protein family, can interact with the cortical actin cytoskeleton and the plasma membrane [46–48]. Ezrin phosphorylation at T567 plays an important role in maintaining cell morphology and specific structure [49, 50], dynamic regulation of B‐cell receptor mobility [51], eight‐cell embryo compaction [52], apoptotic signal transduction [53], etc.…”
Section: Discussionmentioning
confidence: 99%
“…To a great extent, the function of podocytes is based on dynamic regulation of intricate cell structures, especially foot process structures [54]. Ezrin, the actin‐plasma membrane linking protein, is mainly present in the foot processes of podocytes [47, 56], and its phosphorylation at T567 has an essential role in maintaining proper foot process structure [48, 56]. Foot process abnormalities in podocytes and podocyte dysfunction are present in diabetic nephropathy, and a previous study showed that ezrin phosphorylation at T567 was downregulated in the glomeruli of rats with streptozotocin‐induced diabetes [57].…”
Section: Discussionmentioning
confidence: 99%